The effects of processing steps on avenanthramides, avenacosides and β-glucan content during the production of oat-based milk alternatives - Roisin McCarron; Lisa Methven; Sameer Khalil Ghawi; Stephanie Grahl; Ruan Elliott; Stella Lignou (Food Chemistry Advances)
Oat-Based Milk Alternatives (OMAs) may provide health benefits resulting from oat nutritional compounds; avenanthramides, which are polyphenols providing anti-inflammatory and antioxidant effects; avenacosides - saponins with anti-bacterial and anti-fungal properties; and β-glucans, which may assist in lowering blood cholesterol and prevention of diabetes and cardiovascular diseases. Oats undergo multiple processing steps to ensure a sensory appealing and safe product, however, little research has been carried out on the specific effects on these compounds. This study aimed to determine concentration of avenanthramides, avenacoside A and β-glucan in OMA samples throughout 12 stages of production. Avenanthramides and avenacosides were measured using liquid chromatography-mass spectrometry, with β-glucan determined spectrophotometrically using a modified enzymatic assay.An overall reduction of 42 % was observed in measured β-glucan, with a decanting stage a main contributing factor. Measured β-glucan was negatively impacted by glucoamylase treatment, yet increased upon α-amylase, 90 °C and high shear treatments. Avenanthramides and avenacoside A significantly increased after initial enzymatic treatment with α-amylase, whilst avenanthramides increased again upon 90 °C heat treatment and decanting. However, avenanthramide concentration decreased after UHT and prolonged heat treatments, suggesting a susceptibility to degradation at temperatures above 120 °C. With this information, future production may be optimised to better preserve potential health benefits of OMAs.